Acupuncture for women with refractive Overactive Bladder Syndrome - Cloete, Marinus (Department of Obstetrics and Gynaecology, 2014)
To evaluate the efficacy of acupuncture in refractive OAB. The primary aim was to evaluate the effect on frequency, nocturia and urge urinary incontinence. The secondary aim was to evaluate the effect of the response on self-perceived quality-of-life.